2019
DOI: 10.1021/acs.orglett.9b03103
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Promoted Selective Imination of Unactivated C–H Bonds via Copper-nitrene Intermediates for the Synthesis of 2H-Azirines

Abstract: A novel strategy to trap iminyl radicals with copper ions has been developed at room temperature, the resulted high-valent Cu­(III) imine intermediate resets quickly to form nitrene and then to furnish a 2H-azirine. This protocol with dual copper/photoredox catalyst enables the selective imination of unactivated C–H bonds under mild conditions with a broader scope. Moreover, this method also uncovers a novel ring-expansion rearrangement from cyclobutyl oxime derivatives to give the α-acylamino cyclopentanones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Given these unique reactivities, we propose that, in our case, the free iminyl radicals undergo direct Au–N bonding reactions with Au electrodes, thus enabling the formation of single-molecule junctions. Note that, as suggested by previous studies, the reactions between N-centered radicals and transition metals may form covalent metal-N bonds by quenching the radicals . It is also possible that the radical binds to the metal surface via the N lone pair and produces a metal-bound radical intermediate .…”
Section: Resultsmentioning
confidence: 54%
“…Given these unique reactivities, we propose that, in our case, the free iminyl radicals undergo direct Au–N bonding reactions with Au electrodes, thus enabling the formation of single-molecule junctions. Note that, as suggested by previous studies, the reactions between N-centered radicals and transition metals may form covalent metal-N bonds by quenching the radicals . It is also possible that the radical binds to the metal surface via the N lone pair and produces a metal-bound radical intermediate .…”
Section: Resultsmentioning
confidence: 54%
“…Azirines 218 were synthesized by the irradiation of oxime esters 217 with blue light in the presence of the fac ‐Ir(ppy) 3 /CuBr catalytic system (Scheme 84). [156] The authors suggested that at the first stage of the reaction, the one‐electron reduction of oxime ester 217 by fac ‐Ir(ppy) 3 occurs with the formation of the iminyl radical. The latter is intercepted by Cu I .…”
Section: Other Reactions Of Oxime‐derived Iminyl Radicalsmentioning
confidence: 99%
“…Based on the clues from our mechanistic investigations 23 and previous reports, a plausible reaction mechanism was depicted in Scheme 5. Initially, the excited Ir(III) catalyst (E 1/2 (Ir(III)*/Ir(IV)) = À1.73 V vs. SCE) 24 would be able to conduct a SET reduction of 1a (E red (1a/1a À ) = À1.78 V vs. SCE) (see the ESI † for details) to release the nitrogen-centered radical A, [9][10][11]19,25 which is trapped by Cu(I) to yield imino-Cu(II) complex B. The subsequent isomerization of B gives Cu(II) intermediate C. 17b-d,13b Concurrently, the cyano radical species, generated from the reaction of the Cu(II) salt and TMSCN, delivers dicyano-substituted iminyl radical E and Cu(I).…”
mentioning
confidence: 99%
“…Therein, functionalized ketones 10 can be straightforwardly synthesized from oxime esters. In addition, diverse three- and five-membered nitrogen-containing heterocycles, including 2 H -azirines, 11 pyrroles, 12 pyrazoles, 13 oxazoles, 14 thiazoles, 15 and imidazoles, 16 have been efficiently constructed. The elegant syntheses of six-membered heterocycles such as pyridines, 17 quinolines, 18 phenanthridines, 19 and pyrimidines 20 have also been achieved (Scheme 1a).…”
mentioning
confidence: 99%